Position Paper: Overview of Workplace Bullying in Higher Educational Organizations - Monique J. Grant Coke (Journal of Human Psychology, 2021)
Bullying in higher education among educators has been researched at the international level and the present evidence strongly exists with need for further research regarding prevention 23456. Strong empirical research has been published on bullying with viewpoints on the damages to leadership, supervision, incivility and abuse experienced by educators 1256. Bullying in higher educational organizations has been observed with antecedents of power, “wanting to get ahead”, favoritism, and other precursors and challenges of incivility leading to bullying 1234. Workplace bullying antecedents and effects, describe the possible experiences, background, and precursors, that would reveal workplace bullying 12. Bullying in higher academia can result from behaviours and experiences that show humiliation, overtalking others, aggression, exclusion of others, disengagement of employees, among other subtle ways of silencing others 12347. It is therefore still important that educators continue to have a positive, purposeful and productive research driven approach towards solutions for preventing bullying in educational organizations.
Keywords: leadership